PENGARUH INVESTMENT OPPORTUNITY SET, CORPORATE SOCIAL RESPONSIBILITY, DAN RISIKO BISNIS TERHADAP NILAI PERUSAHAAN - Muhammad Fuad Alamsyah; Widyawati Malanua (Jurnal Fokus Manajemen Bisnis, 2021)
This study aims to determine the effect of investment opportunity set, corporate social responsibility and business risk on firm value. Investment opportunity set is measured using market book value equity, capital expenditure to book value of assets and corporate social responsibility is measured by corporate social responsibility disclosure index and business risk is measured by business risk in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. the method of determining the sample using purposive sampling then obtained a sample of 39 companies. The data analysis technique used is multiple regression analysis. The results showed that the investment opportunity set consisting of market book value equity had a significant effect on firm value, capital expenditure to book value of assets had no significant effect on firm value, corporate social responsibility had a significant effect on firm value, and business risk had no effect on firm value.